2021
DOI: 10.1371/journal.pone.0260675
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of hepatocellular carcinoma in type 2 diabetes patients: A two-centre study in a developing country

Abstract: Type 2 diabetes mellitus (T2DM) is increasingly known as a risk factor of hepatocellular carcinoma (HCC). In this study, we determined the risk factors associated with HCC in T2DM patients. This was a matched case-control study conducted at two hepatobiliary referral centres in a developing country. Patients’ sociodemographic, clinical, and biochemical characteristics between 1 January 2012 and 30 June 2018 were extracted from the electronic medical records and analysed using multivariate logistic regression a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 73 publications
2
8
0
Order By: Relevance
“…The variance inflation factor (VIF) of all included variables ranges from 1.18-1.79, suggested no multicollinearity problem among the included variables [ 26 ]. This finding had been discussed in detail in the previous literature [ 19 ].…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…The variance inflation factor (VIF) of all included variables ranges from 1.18-1.79, suggested no multicollinearity problem among the included variables [ 26 ]. This finding had been discussed in detail in the previous literature [ 19 ].…”
Section: Resultssupporting
confidence: 77%
“…The multiple logistic regression (MLR) analysis showed that ten variables were significantly associated with HCC development after adjustment for age, sex, race, DM duration, blood transfusion, smoking, traditional medication, metformin, gliclazide, insulin, HbA1c, RBC, WBC, total bilirubin, and creatinine. These independent factors are; weight loss (adjusted odd ratio [AOR] = 5.28, 95% CI: 2.29; 12.19), having abdominal pain/discomfort (AOR = 6.73, 95% CI: 3.34; 13.34), viral hepatitis infection which interacted with Malay (AOR = 11.77, 95% CI: 1.39; 99.79) and Chinese race (AOR = 37.94, 95% CI: 3.92; 367.61), non-alcoholic fatty liver disease (AOR = 3.29, 95% CI: 1.40; 7.76), statins usage (AOR = 0.37, 95% CI: 0.21; 0.65), history of alcohol consumption (AOR = 4.08, 95% CI: 1.81–9.22), reduced platelet level <150 × 103/μL (AOR = 4.03, 95% CI:1.90; 8.55), ALP level >129 IU/L (AOR = 2.17, 95% CI:1.17; 4.00) and raised ALT ≥25 IU/L (AOR = 2.11, 95% CI: 1.16; 3.86) [ 19 ]. The variance inflation factor (VIF) of all included variables ranges from 1.18-1.79, suggested no multicollinearity problem among the included variables [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations